1999
DOI: 10.1002/(sici)1097-4644(19991215)75:4<652::aid-jcb11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential IGF-independent effects of insulin-like growth factor binding proteins (1-6) on apoptosis of breast epithelial cells

Abstract: We have demonstrated previously that insulin-like growth factor binding protein (IGFBP)-3 alone has little growth inhibitory effect on Hs578T human breast cancer cells, but that it can dramatically accentuate the apoptotic response to the physiological trigger, ceramide, in an IGF-independent manner. We have now studied the potential of other IGFBPs (1-6) to interact with apoptotic signalling pathways. Hs578T cells were preincubated with a binding protein (100 ng/ml) for 24 h, followed by co-incubation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…Specifically, expression of the IGFBP4 and IGF receptor 2 genes was inversely associated with survival and expression of IRS2 was positively associated with survival even when controlled for other clinical prognostic factors. While the precise biologic role of these genes in ovarian cancer remains to be investigated, a previous in vitro report suggested that IGFBP4 prevents breast cancer cell apoptosis, a role compatible with the expression pattern observed in our dataset (Perks et al 1999). On the other hand, the IGF-II receptor facilitates internalization/degradation of the IGF-II ligand (O'Dell & Day 1998), while the IRS2 is thought to modulate IGF signaling.…”
Section: Spentzos Et Al: Igf Axis Expression and Survival In Eocsupporting
confidence: 82%
“…Specifically, expression of the IGFBP4 and IGF receptor 2 genes was inversely associated with survival and expression of IRS2 was positively associated with survival even when controlled for other clinical prognostic factors. While the precise biologic role of these genes in ovarian cancer remains to be investigated, a previous in vitro report suggested that IGFBP4 prevents breast cancer cell apoptosis, a role compatible with the expression pattern observed in our dataset (Perks et al 1999). On the other hand, the IGF-II receptor facilitates internalization/degradation of the IGF-II ligand (O'Dell & Day 1998), while the IRS2 is thought to modulate IGF signaling.…”
Section: Spentzos Et Al: Igf Axis Expression and Survival In Eocsupporting
confidence: 82%
“…In prostate 17 and mammary 18 glands and in the rat brain following hypoxic-ischemic injury, 19 increased expression of IGFBP-5 has been associated with apoptotic processes. In contrast, Perks et al 20 have demonstrated a protective effect of IGFBP-5 in human breast cancer cells following a proapoptotic stimulus with ceramide. Also in cerebellar granule cells, the induction of apoptosis has been associated with downregulation of IGFBP-5.…”
Section: Introductionmentioning
confidence: 89%
“…In breast cancer cells, the binding of IGFBP-1 to integrin at the cell surface resulted in dephosphorylation of FAK, detachment from the ECM, and cellular apoptosis (Perks et al, 1999). A proapoptotic action of IGFBP-3 has also been reported to be independent of IGF (Perks et al, 1999a(Perks et al, , 1999bButt et al, 2000;Maile et al, 1999). A number of potential IGF-independent survival-promoting effects of IGFBP-4 and IGFBP-5 have been reported; however, the mechanisms underlying these effects are not known (Perks et al, 1999a).…”
Section: Igfbpsmentioning
confidence: 99%
“…A proapoptotic action of IGFBP-3 has also been reported to be independent of IGF (Perks et al, 1999a(Perks et al, , 1999bButt et al, 2000;Maile et al, 1999). A number of potential IGF-independent survival-promoting effects of IGFBP-4 and IGFBP-5 have been reported; however, the mechanisms underlying these effects are not known (Perks et al, 1999a). Finally, IGFBP-3 and IGFBP-5 are translocated into the nucleus via the importin-5 subunit (Schedlich et al, 1998(Schedlich et al, , 2000.…”
Section: Igfbpsmentioning
confidence: 99%